Pengaruh Penggunaan Aplikasi Canva Melalui Smartphone terhadap Kemampuan Guru Taman Kanak-kanak dalam Membuat Media Pembelajaran - Ramadhani, Nurhidayah; Mardiyah, Taufikah Ridha; Jannah, Miftahul; Hestiliani, Asa (Medan Resource Center, 2025)
This study investigates the impact of using the Canva application via smartphones on the ability of kindergarten teachers to develop effective and creative learning media in Pangkep Regency. The research was motivated by the need to improve the quality of early childhood education through the integration of accessible digital tools. The central research question focuses on whether Canva significantly enhances teachers' creativity compared to traditional methods. Employing a quantitative approach with a posttest-only control group design, the study involved 60 kindergarten teachers selected through random sampling. Data were gathered through structured observation and analyzed using nonparametric statistical methods, following normality and homogeneity testing. The results indicate a significant improvement in the creativity of teachers who utilized Canva, demonstrating its potential as an effective digital tool in early education settings. The findings suggest that training programs centered on Canva can empower teachers to design more engaging, visually appealing, and pedagogically sound media, ultimately contributing to better learning experiences for young children.